Determinant Factors of Audit Quality - ARIE WIBOWO; HILDA ROSSIETA (The Indonesian Journal of Accounting Research, 2013)
This study is aimed at examining the determinant factors of audit quality. Different from the previous studies, we use earnings surprise benchmark developed from Carey and Simnet (2006) as the proxy for audit quality. Based on the previous literature, we expect that audit tenure, size of audit firm, and audit regulation have a positive impact on audit quality. Using logistic model,we find that size of audit firm and audit regulation are the two determinant factors that consistently provide positive effect on audit quality. This result suggests that the probability for delivering high audit quality increases as the audit firm size is getting bigger. In addition, the probability of high audit quality is higher under audit regulation regime compared to that of non-regulated.